Rajendra S. Sisodia, David B. Wolfe & Jagdish N. Sheth, Firms of Endearment: How World-Class Companies Profit from Passion and Purpose - Παπαδόπουλος Ιορδάνης (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2015)
[Δεν διατίθεται περίληψη / no abstract available]